POTENTIAL ANALYSIS OF GAYO ARABICA COFFEE DERIVATIVE PRODUCTS AT KBQ BABURRAYYAN CENTRAL ACEH (Case Study of KBQ Baburrayyan) - Yoga Nugroho; Rusdi Faizin; Dedy Darmansyah; Lusiana (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
Gayo Arabica Coffee is one of the leading commodities which is an Arabica coffee variety originating from the Gayo Highlands, with the best taste. Gayo coffee is also in demand by the international community because it has a taste and the development of Gayo Arabica coffee has also been processed into various kinds of Gayo Arabica Coffee Derivative Products with the development of innovations like this will be a potential product advantage to develop in a sustainable manner. The purpose of this research is to make a decision to determine superior products that will develop sustainably at KBQ Baburrayyan. the method used is the Analytical Hierarchy Process to process qualitative data into a form of quantitative data.